Manual Oyster Shucking Technique: A Case Study at Nozomi Suishan Company, Okayama, Japan - Abraham Luther; Junianto (Grouper, 2024)
Manual oyster shucking is a crucial process in the seafood processing industry that significantly impacts the quality and value of the final product. This study investigates the manual oyster shucking techniques employed by Nozomi Suishan Company in Okayama, Japan. Observational methods and interviews were used to understand the shucking procedures, challenges faced, and efforts to improve efficiency in the process. The research findings indicate that the use of traditional tools and operator skills play a key role in the success of this process. This study provides important insights for the seafood processing industry to enhance operational efficiency and maintain the quality of the final product.